A tunable reflection‐type filtering phase shifter using SISL technology. Issue 11 (15th July 2022) - Yang, Jianteng; Ma, Kaixue; Fu, Haipeng; Wang, Yongqiang; Chen, Xiong; Yan, Ningning
Abstract: This letter proposed a novel tunable reflection‐type phase shifter (RTPS) with a filtering function using substrate‐integrated suspended line (SISL) technology. First, a novel 3‐dB branch‐line coupler with a filtering function is designed by using broadside coupling lines. On this basis, the filtering RTPS is realized by combining with a series varactor network. The proposed SISL filtering RTPS can obtain a continuous phase shift range of 104° under 0–30 V DC bias control, which enables multifunctional integration of phase shifters. All circuits are implemented on the SISL platform, which has the advantages of double‐sided wiring, self‐packaging, and low loss.